Generation of Single‐Chain Variable Fragment (scFv) Libraries for Use in Phage Display. Issue 7 (7th July 2021) - Schladetsch, Megan A.; Wiemer, Andrew J.
Abstract: Phage display is a powerful platform for the discovery of novel biologics with high binding affinities to a specific target protein. Here, we describe methods to construct a phage display library containing diverse single‐chain variable antibody fragments (scFvs). Specifically, updated methods for polymerase chain reaction (PCR) amplification and fusion of human antibody genes, their ligation into the pComb3X vector for transformation into 5αF′I q competent bacterial cells, and their expression in M13KO7 helper phage are presented. Additionally, we describe how to amplify and quantify the phage library and to prepare it in various formats for short‐ and long‐term storage. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : First‐round polymerase chain reaction (PCR) for isolation of antibody fragments Basic Protocol 2 : Ethanol precipitation and pooling of fragment DNA Basic Protocol 3 : Second‐round polymerase chain reaction with splicing by overlap extension (SOE) for antibody fragment fusion Basic Protocol 4 : Restriction digestion of individual scFv constructs and pComb3XSS vector Basic Protocol 5 : Directional ligation of the scFv constructs and pComb3X backbone Basic Protocol 6 : Transformation of pComb‐scFv plasmids into 5αF′I q competent cells Basic Protocol 7 : Collection of bacteria containing the scFv library Basic Protocol 8 : Preparation of bacterial glycerol stock Basic Protocol 9 : Preparation of phage library glycerol stock Basic Protocol 10 : Preparation of plasmid DNA stock Basic Protocol 11 : Amplification of M13KO7 helper phage Basic Protocol 12 : Phage titer by plate assay Alternate Protocol : One‐plate phage plaque assay